2011
DOI: 10.3109/15563650.2011.560854
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom poisoning in Ireland: The collaboration between the National Poisons Information Centre and expert mycologists

Abstract: Poison information centres should maintain a registry of expert mycologists who are available for consultation following potentially serious mushroom intoxications. Health care workers should not attempt to identify toxic mushroom species using the Internet as erroneous identification can occur. Digital photography may help with mushroom identification when there is likely to be a delay organising a physical examination of mushroom tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 15 publications
2
16
0
1
Order By: Relevance
“…35 Interesting perspective emerges from innovative molecular biology techniques adapted to be used with gastric aspiration fluids or cooked mushrooms, but they are yet not ready for prime time in clinical practice due to the high cost, the need for skilled personnel, and the long turnaround time. 36 As in other studies, we identified a high prevalence of edible mushrooms causing ED presentation. 9,13,32 In agreement with two previous Swiss studies, B. edulis was the most frequent species.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…35 Interesting perspective emerges from innovative molecular biology techniques adapted to be used with gastric aspiration fluids or cooked mushrooms, but they are yet not ready for prime time in clinical practice due to the high cost, the need for skilled personnel, and the long turnaround time. 36 As in other studies, we identified a high prevalence of edible mushrooms causing ED presentation. 9,13,32 In agreement with two previous Swiss studies, B. edulis was the most frequent species.…”
Section: Discussionsupporting
confidence: 72%
“…35 Interesting perspective emerges from innovative molecular biology techniques adapted to be used with gastric aspiration fluids or cooked mushrooms, but they are yet not ready for prime time in clinical practice due to the high cost, the need for skilled personnel, and the long turnaround time. 36…”
Section: Discussionmentioning
confidence: 99%
“…1,4 The diagnosis of mushroom poisoning should be based on mushroom identification, clinical features, and laboratory analyses. 9 Mushrooms have numerous spores characteristic for each species. 10,11 The gastric contents, the reminder of a mushroom dish, and the whole mushrooms themselves are subject to evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…17 With regard to poisonous fungi, the importance of precise identifications by specialists is clear, and this has been highlighted in several studies. 18,19 There can be surprises even with supposedly well-known fungi purchased in stores. Recently, molecular work showed that a packet of dried "porcini mushrooms (Boletus edulis)" bought in a London shop, contained a mixture of three Boletus species that were new to science; 20 fortunately in this case they appear not to have been poisonous species of the genus.…”
Section: Psychotropic and Toxic Substancesmentioning
confidence: 99%